Influences of compatibilizer type and loading on properties of phenolic resin-crosslinked natural rubber composites filled with sepiolite - Nabil Hayeemasae; Siriwat Soontaranon; Abdulhakim Masa (eXPRESS Polymer Letters)
Natural rubber (NR) composites reinforced with sepiolite and crosslinked with phenolic resin were prepared. Effects of compatibilizer types and contents, namely 3-aminopropyl triethoxysilane (APTES) or epoxidized NR (ENR50), on curing, tensile, strain-induced crystallization, and stress relaxation were investigated. Compared to APTES, ENR50 provided a greater compatibilizing effect in the NR composites. The ENR50 introduced strong physical and chemical interactions between sepiolite and NR, while only physical interaction was present in the APTES compatibilized composites. Stronger interaction between rubber and sepiolite improved filler dispersion, swelling resistance, and tensile strength; and delayed stress relaxation of the composite. Increased addition of ENR50 improved the modulus and tensile strength, and the greatest tensile strength was achieved at 2 phr ENR50 with a 15% improvement over composite without compatibilizer. In the case of APTES, 2 phr level enhanced tensile strength, but a further increase in APTES content degraded tensile, swelling resistance, and stress relaxation responses, due to its plasticizing effect. Moreover, ENR50 enhanced the strain-induced crystallization and delayed stress relaxation of the composites more than APTES. Weaker interaction between rubber and filler in APTES filled composites was due to having only hydrogen bonds formed between rubber and filler, in addition to crosslinks.